2021
DOI: 10.1093/ntr/ntab098
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Public Sentiments About JUUL Flavors on Twitter Through Machine Learning

Abstract: Introduction The availability of a variety of e-cigarettes flavors is one of the frequently cited reasons for their adoption. An active stream of discussion about flavoring can be observed online. Analyzing these real-time conversations offers nuanced insights into key factors related to the adoption of flavors, subsequently supporting public health interventions. Methods Google’s BERT, a state-of-the-art deep learning method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…N-grams connected sequences of n items (words) from a given sample of text or speech (Broder et al, 1997). We examined top unigrams, bigrams, and trigrams and found that the trigrams were the most interpretable for salient content themes, consistent with previous social media tobacco research (Benson et al, 2020; Czaplicki, Kostygina, et al, 2020; Malik et al, 2021; N. Silver et al, 2022).…”
Section: Methodssupporting
confidence: 74%
“…N-grams connected sequences of n items (words) from a given sample of text or speech (Broder et al, 1997). We examined top unigrams, bigrams, and trigrams and found that the trigrams were the most interpretable for salient content themes, consistent with previous social media tobacco research (Benson et al, 2020; Czaplicki, Kostygina, et al, 2020; Malik et al, 2021; N. Silver et al, 2022).…”
Section: Methodssupporting
confidence: 74%
“…The e-cigarette products in the market usually offer a very wide variety of flavoring agents mixed with nicotine, which is one of the biggest health concerns of e-cigarettes ( Rambaran et al, 2019 ; Malik et al, 2021 ). Here, we aim to evaluate whether the social functioning is modified by ENDS with a flavoring compound.…”
Section: Resultsmentioning
confidence: 99%
“…E-cigarette products in the market are usually offer a very wide variety of flavoring agents mixed with nicotine, which is one of the biggest health concern for e-cigarettes [36, 37]. We here aim to evaluate whether the rewarding effects of ENDS can be modified by flavoring compound in e-cigarette.…”
Section: Resultsmentioning
confidence: 99%